A comparison of major trauma patient transport destination in metropolitan Perth, Western Australia - Brown, Elizabeth; Tohira, Hideo; Bailey, Paul; Fatovich, Daniel; Pereira, Gavin; Finn, Judith (2019)
Background: Despite evidence of a lower risk of death, major trauma patients are not always transported to Trauma Centres. This study examines the characteristics and outcomes of major trauma patients between transport destinations. Methods: A retrospective cohort study of major trauma patients (Injury Severity Score >15) transported by ambulance was undertaken. Cases were divided into transport destination groups: (1) Direct, those transported to the Trauma Centre directly from the scene; (2) Indirect, those transported to another hospital prior to Trauma Centre transfer and (3) Non-transfers, those transported to a non-Trauma Centre and never subsequently transferred. Median and interquartile range (IQR) were used to describe the groups and differences were assessed using the Kruskal–Wallis test for continuous variables and Pearson chi-square for categorical. Results: A total of 1625 patients were included. The median age was oldest in the non-transfers cohort (72 years IQR 46–84). This group had the highest proportion of falls from standing and head injuries (n = 298/400, 75%, p < 0.001). The non-transfers had the highest proportion of 30-day mortality (n = 134/400, 34%). Conclusions: There were significant differences between the groups with older adults, falls and head injuries over-represented in the non-transfer group. Considering the ageing population, trauma systems will need to adapt.